Implementasi Kebijakan Pengarusutamaan Gender pada Bidang Pendidikan di Dinas Pendidikan Kabupaten Tangerang - Naila Lutfia Agustari; Izzatusholekha Izzatusholekha (STIKes Ibnu Sina Ajibarang, 2025)
The main issue addressed in this study is the gap between normative policies and actual practices regarding gender mainstreaming (GMS) at the Education Office of Tangerang Regency. The aim of this study is to analyze the implementation of GMS policies using Smith's theory, which includes ideal policy indicators, target groups, implementing organizations, and environmental factors. This research uses a descriptive method with a qualitative approach. Data collection techniques include in-depth interviews, observations, and documentation. The results show that first, the ideal policy is outlined in Regent Regulation No. 10 of 2019; however, it has not been systematically elaborated in the Strategic Plan (RENSTRA) and Work Plan (RENJA) of the Education Office, limiting its implementation. Second, the target groups, such as teachers, students, and the general public, have not fully understood the concept of GMS, as the dissemination of information remains minimal and unfocused. Third, the implementing organization, the Education Office, has not yet optimized coordination in implementing GMS with schools, nor provided comprehensive, specialized training. Fourth, environmental factors, such as strong gender stereotypes, limited gender-friendly facilities, and low public awareness, are significant challenges in the policy’s implementation. Based on these findings, it can be concluded that the implementation of GMS policies at the Education Office of Tangerang Regency remains symbolic and requires strengthening of institutions, more intensive socialization, and active involvement of all stakeholders to achieve more optimal success.